2019
DOI: 10.1055/s-0038-1676777
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Defect Size is Associated with Increased Complication Rate after Free Tissue Transfer for Midanterior Skull-Base Reconstruction

Abstract: Objective Complications after skull-base reconstruction are often problematic. We consider that local factors, for example, localization of defect areas are possible risk factors. This study aimed to investigate our case series of skull-base reconstructions in our institution and to identify local risk factors that predispose to wound complications. Design This study is presented as a retrospective study. Setting Research work was took place at Nagoya University Hospital. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…Many publications have reported postoperative complications of free ap for skull base reconstruction and its risk factors. The overall complication rate of a variety of the free aps is 10-32%, and partial or complete ap failure occurs in 2-9% [3,25,26,12,7,27]. The overall incidence of complications in this series was 17.6% and the rate of ap loss was 5.9%, which compared well with the literature.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Many publications have reported postoperative complications of free ap for skull base reconstruction and its risk factors. The overall complication rate of a variety of the free aps is 10-32%, and partial or complete ap failure occurs in 2-9% [3,25,26,12,7,27]. The overall incidence of complications in this series was 17.6% and the rate of ap loss was 5.9%, which compared well with the literature.…”
Section: Discussionsupporting
confidence: 80%
“…However, no CSF leaks occurred in our cohort, which may be due to our careful closure of the dural defects (fascia lata graft, fat strips and vascularized ap). It has been reported that history of radiation therapy, medical comorbidities and the extent of intracranial tumor extension were independent predictors of complication rate [26]. Thompson et al [28] supposed that there was a higher wound complication rate in those with a history of smoking and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The free tissue flap has several disadvantages in the sense that not suitable for significant defects, delayed healing could be dislodged, and the need for another incision in the donor site. A vascularized flap provides a reliable reconstruction of significant skull base defects with low rates of post-operative CSF leak when compared to free tissue grafts (6)(7)(8)(9) .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A vascularized flap provides a reliable reconstruction of significant skull base defects with low rates of postoperative CSF leak when compared with free tissue grafts. [6][7][8][9] Local vascularized flaps gained wide acceptance and became the principal reconstructive choice due to their advantages (e.g., ease of elevation, low morbidity of the donor site, low rate of complications, and the tendency for rapid and complete healing). The nasoseptal flap (NSF) has become the mainstay of endonasal reconstruction as it is versatile, has a good arc of rotation, and provides a large surface area.…”
Section: Introductionmentioning
confidence: 99%
“…The great majority of CFS need a reconstruction after surgical resection, and a variety of techniques (regional pedicled flaps or free flaps) must be employed in order to establish a barrier between the intracranial and extracranial structures, thus preventing cerebrospinal fluid (CSF) leaks and ascending infections to reduce the frequency of surgical wound complications [14,15 ▪ ]. Dias et al [3] evaluated 57 patients with CFS for NMSC and identified that extensive facial disease (destructive lesions with direct invasion of the anterior cranial cavity) and the reconstruction with free flaps were the most important risk factors for the development of infectious complications.…”
Section: Surgical Managementmentioning
confidence: 99%